The Slang Words from Turning Red Movie Script - Shan Derwin Susanto; Luh Putu Laksminy; Ni Luh Putu Krisnawati (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
This study examines the types and functions of slang words in the movie script of